Atherosclerosis - Yeldir, Neşe (Nova Science Publishers, Inc., 2024)
Atherosclerosis is a multifocal immunoinflammatory disease of the medium-sized and large arteries. Atherosclerosis mainly causes diseases such as myocardial infarction and stroke, which are the leading causes of mortality worldwide. In addition to genetic, age, male sex, and environmental factors for the development of atherosclerosis, there are also known risk factors such as hypercholesterolemia, hypertension, diabetes mellitus, and smoking. In the early stages, the cause of atherosclerosis is endothelial injury. Inflammatory cells, smooth muscle cells, and endothelial cells are the primary elements in the development of atheromatous plaque. Inflammation has an important role in the initiation and progression of atheromatous plaque. Ruptured plaques include a fibrous cap and a lipid-rich core, which contain inflammatory cells, smooth muscle cells, and angiogenesis. Plaque rupture is one of the main causes of thrombosis. Atherosclerosis is mortal due to events such as acute coronary syndromes and strokes caused as a result of thrombosis accompanying a ruptured or eroded atheromatous plaque. Thrombosis can partially or completely block the vascular lumen and, as a result, cause ischemic findings. The main clinical results of atherosclerosis are myocardial infarction, stroke, aortic aneurysm, and peripheral vascular disease.
Keywords: Atheromatous Plaque; Atherosclerosis; Endothelial Cell; Fibrous Cap; Inflammation; Vascular Disease